Early failure mechanism research of electromechanical product based on meta-action. (April 2021) - Li, Yulong; Wu, Chuang; Zhang, Xiaogang; Ran, Yan; Zhang, Genbao
Highlights: A more reasonable analysis object (meta-action and meta-action unit) is selected. A failure mode quantitative judgment method based on meta-action is proposed. A new failure cause and mechanism modeling method based on meta-action is proposed. Abstract: Early failure is the key factor that restricts the improvement of electromechanical product reliability. The research on early failure mechanism of electromechanical product can provide a basis for the subsequent failure cause tracing and failure diagnosis. At present, there are few systematic studies on the early failure mechanism of electromechanical product, which have the following shortcomings: firstly, the failure analysis objects in traditional failure methods cannot reflect the characteristic of electromechanical product that "motion determination electromechanical product function"; secondly, traditional failure analysis methods ignore the fact that mechanical and electronic systems are different in failure cause, failure mode and failure mechanism; thirdly, failure cause and failure mode are easily confused in traditional methods; finally, most of the traditional methods are qualitative analysis, which cannot directly show the generation process of failure. To address those problems, meta-action and meta-action unit of electromechanical product are selected as the analysis object herein. Early failure mode, early failure cause, and early failure mechanism of electromechanical product are defined and analyzed. A meta-action early failure mechanism quantitative analysis model considering electromechanical coupling is built, and the influence of failure cause on failure mode is analyzed. A CNC (computer numerical control) machine tool made in China is taken as an example. The results verify the applicability and correctness of the proposed method.